Semiconductor Heterojunction Design: Database‐Driven Materials Selection for Semiconductor Heterojunction Design (Adv. Theory Simul. 10/2018). Issue 10 (4th October 2018) - Shapera, Ethan P.; Schleife, André
Abstract : Interfaces between semiconductors, like between CdTe and InSb pictured here, can present subtle atomic geometries and intricate electronic‐structure features, that render a detailed understanding of band alignment difficult. In article1800075, Ethan P. Shapera and André Schleife employ an approximate approach which rapidly screens an existing online database to facilitate semiconductor heterojunction design. Rob Sisneros and Blue Waters are acknowledged for help creating this image.